ANTICORRUPTION FUNCTIONS OF THE AUTHORITIES IN CHARGE OF PREVENTION OF CORRUPTION AND OTHER OFFENCES OF THE RUSSIAN FEDERATION SUBJECTS - P. A. Kabanov (Russian Journal of Economics and Law, 2016)
Objective: to identify and systematize the anti-corruption functions of the bodies of the Russian Federation subjects in the sphere of prevention of corruption and other offences on the basis of the analysis of federal and regional normative legal acts on organization of activities of these bodies. Methods: the methodological basis of the conducted research is the dialectical materialism based on scientific methods of cognition: analysis, synthesis, comparison, and other methods used in the legal sciences.Results: the analysis is carried out of federal and regional normative legal acts regulating activities of bodies of the Russian Federation subjects on prevention of corruption and other offences; the basic and advanced functions of the regional anti-corruption authorities to prevent corruption and other offences are identified, classified, systematized, described and explained. Measures are proposed for improvement of legal regulation of activity of bodies of the Russian Federation subjects on prevention of corruption and other offences.Scientific novelty: for the first time in the Russian juridical science, the list is composed of the main (organizational-executive and organizational- provisional) and additional anti-corruption functions of the bodies of the Russian subjects for prevention of corruption and other offences. Practical significance: the research results allow to improve the normative legal acts for organization of the activity of the bodies of the Russian subjects for prevention of corruption and other offences.